1998
DOI: 10.1046/j.1525-1470.1998.1998015169.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Infectious Purpura Fulminans: Pathogenesis and Medical Management

Abstract: Purpura fulminans (PF) is a potentially disabling and life-threatening disorder characterized by acute onset of progressive cutaneous hemorrhage and necrosis, and disseminated intravascular necrosis. Acute infectious PF occurs most commonly in the setting of meningococcemia due to elaboration of endotoxin. Presence of purpura, particularly when generalized, is an important predictor of a poor outcome following meningococcal infection. Histopathologic hallmarks of acute infectious PF are dermal vascular thrombo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
99
0
13

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(112 citation statements)
references
References 132 publications
0
99
0
13
Order By: Relevance
“…A few reports describe PF in children, and most of the cases are related to infectious disease such as meningococcemia, varicella, or pneumococcal disease or to severe congenital PC or PS deficiency [1,5,11]. Congenital and acquired risk factors in childhood PF are largely unknown, and additionally, with effective immunization programs against viral infections and better health care provided to children, one may expect changes in the rate of participating infections in PF.…”
Section: Introductionmentioning
confidence: 99%
“…A few reports describe PF in children, and most of the cases are related to infectious disease such as meningococcemia, varicella, or pneumococcal disease or to severe congenital PC or PS deficiency [1,5,11]. Congenital and acquired risk factors in childhood PF are largely unknown, and additionally, with effective immunization programs against viral infections and better health care provided to children, one may expect changes in the rate of participating infections in PF.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is one of the earliest reports of falciparum malaria complicated with PF in an endemic malaria setting and involving children. Previous studies have shown that 60 to 70% cases of acute purpura fulminans occur amongst children below two years of age [13]. The two previous cases of PF reported previously in Nigeria involved a two month old and three year-old with symmetric gangrene.…”
Section: Discussionmentioning
confidence: 87%
“…Cumulatively these changes might explain the pathogenesis behind the thrombocytopenia and intravascular platelet aggregation. Transfusion of coagulation factor, protein C, protein S, antithrombin III concentrates, have been shown to be beneficial in patients with PF and DIC [1,13].…”
Section: Discussionmentioning
confidence: 99%
“…iii) Acute infectious purpura fulminans, occurs in conjunction with acute infectious illness, particularly sepsis with endotoxin (lipopolysaccharide) producing gram-negative bacteria. [2] Sepsis-induced purpura fulminans is a rare but life-threatening disorder. Meningococcal sepsis is the most common cause.…”
Section: Discussionmentioning
confidence: 99%